Media dan Mitos: Framing Kusni Kasdut Sebagai Legenda Kriminal - Fajar Kurniawan; RR. Rosita Cindrakasih; Angghi Muliya Ma’mur; Hani Yuniani (Lembaga Teewan Journal Solutions, 2026)
This article analyzes the dynamics of the myth-making of Kusni Kasdut (1929–1980) through the lens of mass media framing in the 1960s–1980s in the context of postcolonial Indonesia. As a former freedom fighter turned legendary robber, Kusni occupies an ambiguous position between criminality and heroism that triggers a narrative battle between the state and the lower classes. This research uses critical discourse analysis (Fairclough, 2015) and myth-narrative analysis (Campbell, 2020; Turner, 2017). Critical discourse analysis of national and local media coverage, including Kompas and Tempo, as well as official documents and oral sources from the Gang Jangkrik community in Malang and Surabaya. This research explores 32 national and local media articles and interviews with four key informants from the Gang Jangkrik community in Malang and Surabaya. The findings show that the media constructed three dominant frames: (1) criminality as a threat to the state, (2) heroism as an